Comparing problem-focused, solution-focused and combined problem-focused/solution-focused coaching approach: solution-focused coaching questions mitigate the negative impact of dysfunctional attitudes. Issue 1 (2nd January 2020) - Grant, Anthony M; Gerrard, Benjamin
ABSTRACT: Little is known about impact of different types of questions used in coaching. This study compares the relative impact of 1) SF with 2) PF coaching questions and with 3) a combined problem-focused and solution-focused (PF + SF) coaching questions condition. Despite much discussion about the impact of mental health issues in coaching, there has been little research on how coachees' dysfunctional attitudes effect coaching outcomes. 80 participants were randomly assigned to PF, SF or PF + SF coaching conditions. It should be noted that a whole coaching session was not conducted – in an experimental self-coaching exercise participants responded to different types of coaching question: SF questions were more effective than PF questions on all measures. SF questions were also more effective at increasing self-efficacy and decreasing negative affect compared to a combined PF + SF approach. Dysfunctional attitudes were found to have a detrimental impact on negative affect following both PF and PF/SF questions but not SF. Further analysis revealed that PF questions were significantly less effective on decreasing negative affect for participants 'high' in dysfunctional attitudes, but not for those 'low' in dysfunctional attitudes. For those 'low' in dysfunctional attitudes all three coaching styles were equally effective in reducing negative affect. No other significant relationships were observed between dysfunctional attitudes on goal attainment measures. This research suggests that SF approaches are more effective than PF or combined PF + SF. Recommendations for future research and potential implications for coaching practice are discussed.